Benthic invertebrate communities structure in headwater streams with different states of the riparian vegetation conservation - Melo, A. L.U. [UNESP]; Ono, E. R. [UNESP]; Uieda, V. S. [UNESP] (Springer Nature, 2020)
Many studies assess the impact of anthropogenic activities in water bodies using methods that focus on physical, chemical and microbiological characteristics of water. The use of benthic invertebrates as tools for biomonitoring protocols helps the understanding of those impacts, when these modifications cannot be explained only by the water characteristics. We analyzed the environmental characteristics and invertebrate fauna structure in an 80 m extension of streams located in four micro-basins. This reach-scale analysis included streams of three riparian vegetation conservation states: preserved in both riverbanks (forested), removed in both riverbanks for pasture (pasture), and one riverbank with riparian vegetation and another with pasture (intermediate). The environmental data analysis indicated a clear separation between the forested and pasture streams, emphasizing the interaction of the state of riparian vegetation’s preservation with some habitat characteristics, such as width, substrate type and shelter for the fauna. Our initial hypothesis about the benthic invertebrates’ structure was to find in streams with conserved riparian vegetation a benthic fauna composed mainly by groups more specialized and dependent on coarse substrate and plant material imported from the forest and used as shelter and food resource. This hypothesis was confirmed, with higher abundance of groups sensitive to pollution, such as Plecoptera and Trichoptera, mainly in preserved streams. However, when analyzed together the environmental characteristics and the OTUs that best explained the land uses’ differences (RDA analysis), in two micro-basins there was more fauna’s similarity between intermediate and pasture profiles, and in the other two the three profiles differed from each other. These differences may be related not only to reach-scale physical characteristics, but also to catchment-scale attributes of each micro-basin, as the invertebrate distribution and abundance are influenced by a variety of physical/biological factors at different scales. Thus, the study of the possible influence of riparian vegetation conservation states on habitat characteristics and benthic invertebrate structure seems to be dependent on the spatial scale analyzed.
Keywords: Aquatic insects; Land uses; Mesohabitats; Pasture; Reach-scale